The Effects of Visual Attention Span and Phonological Decoding in Reading Comprehension in Dyslexia: A Path Analysis. (14th October 2016) - Chen, Chen; Schneps, Matthew H.; Masyn, Katherine E.; Thomson, Jennifer M.
Abstract : Increasing evidence has shown visual attention span to be a factor, distinct from phonological skills, that explains single‐word identification (pseudo‐word/word reading) performance in dyslexia. Yet, little is known about how well visual attention span explains text comprehension. Observing reading comprehension in a sample of 105 high school students with dyslexia, we used a pathway analysis to examine the direct and indirect path between visual attention span and reading comprehension while controlling for other factors such as phonological awareness, letter identification, short‐term memory, IQ and age. Integrating phonemic decoding efficiency skills in the analytic model, this study aimed to disentangle how visual attention span and phonological skills work together in reading comprehension for readers with dyslexia. We found visual attention span to have a significant direct effect on more difficult reading comprehension but not on an easier level. It also had a significant direct effect on pseudo‐word identification but not on word identification. In addition, we found that visual attention span indirectly explains reading comprehension through pseudo‐word reading and word reading skills. This study supports the hypothesis that at least part of the dyslexic profile can be explained by visual attention abilities. Copyright © 2016 John Wiley & Sons, Ltd.